Síntese e caracterização de sistemas catalíticos com base em compostos organoestânicos(IV) ancorados em sílica e avaliação de suas atividades catalíticas frente a reações de transesterificação - Jesus, Roberta Anjos de (2019)
In this work, the anchoring of Sn(IV) complexes on silica modified with thiols groups was investigated in order to obtain heterogeneous catalysts with potential activity in the transesterification reaction. The anchoring of organotin(IV) catalysts in silica has already been studied by our research group as heterogenized catalytic systems for the production of methyl esters. However, this work aims to minimize leaching of the active tin-based species of the support and, consequently, to improve the catalytic activity in reactions with the reuse of the catalyst. In this study, the anchoring of the following organotin compounds (IV): n-Me2SnCl2, n-Bu2SnCl2, n-Bu2Sn(OMe)2 and n-Bu3SnOMe were investigated, which under homogeneous conditions show excellent catalytic activity in transesterification reactions. The anchoring of the mentioned complexes was carried out from the interaction between these complexes and groups thiols present in the previously modified silica. The anchoring was confirmed by several analytical techniques, among them: medium infrared spectroscopy, Raman spectroscopy, UV-Vis spectroscopy, thermogravimetric analysis, atomic emission optical spectrometry, X-ray scattering energy, electron microscopy of scanning coupled to the energy by X-ray dispersion, nitrogen fisistion and determination of the surface area by the BET method. The SiO2-S-Bu2SnOMe system presented the highest anchored tin content (9.8%) followed by by SiO2-S-Me2SnCl, SiO2-S-SnBu3 and SiO2-S-Bu2SnCl, which presented, respectively, 8.4, 7.6 and 6.0%. The catalytic performance of both the molecular and the supported organotin systems was evaluated in transesterification reactions of ethyl acetate or tricapryline in the presence of methanol. The products were characterized by gas chromatography. Under the conditions employed, all the tin compounds showed catalytic activity in the following order: n-Bu2Sn(OMe)2 > n-Bu2SnCl2 > n-Me2SnCl2 > n- Bu3SnOMe. On the other hand, heterogenized systems, the following trend was observed: SiO2-S-SnBu2OMe > SiO2-S-SnMe2Cl > SiO2-S-SnBu2Cl > SiO2-S-SnBu3 but in all cases with less activity. It was observed the loss of Sn(IV) from the support in the reuse tests, but the catalysts remained active for up to 6 cycles of reuse for ethyl acetate reaction and 8 cycles for tricaprilin. The anchoring of the organometallic compounds of Sn(IV) was shown to be promising in the transesterification reaction.